A Framework for Integrated Sustainability Assessment of Water Cycle Services - Helness, H.; Damman, S.; de Clercq, W.P.; Elema, N.M. (European Journal of Sustainable Development, 2017)
A methodology and a framework for integrated sustainability assessment of water cycle services to be used for analysis of strategic options in integrated water management has been developed. The hypothesis was that a holistic assessment framework based on local data would enable decisionmaking and sustainable development on a local scale in integrated water management. The SUWAM assessment framework was developed using the water cycle services of a small town in Western Cape, South Africa, as case. The point of departure was the municipality’s plan for sustainable development. The suitability of the SUWAM Framework was assessed by comparison with two other frameworks: TRUST, from the EU-project TRUST, and City Blueprint, developed in an EIPwater action group. The comparison demonstrated that a sustainability assessment framework must: (i) be tailored to the local conditions, and (ii) that the perspective of the user, often a decision maker, must be taken into account in the interpretation of results. The methodology used in the development of the SUWAM Framework fulfilled these two criteria and produced results that were recognised as relevant for the studied case by local stakeholders. The methodology is suited for comparison and further analysis of different mitigation and adaptation measures. Keywords: Integrated Water Management, Sustainability Assessment, Water Cycle Services